PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 016 PANDAN AIR KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Iis Satriana; Damahuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated to learn science is still low yields SDN 016 Pandan Air with an average of 59.75. Still centered learning to teachers and students received less encouragement to develop the ability to think that they have so low learning outcomes. The purpose of this research is to improve learning outcomes IPA class IV SDN 016 Pandan Water in the subject matter of the earth and celestial appearance. This research was conducted by the method of action research. Subjects were class IV students of SDN 016 Pandan Water by the number of students 20 people. Instrument research include syllabi, lesson plan, student worksheets. The data analysis using descriptive analysis. Learning outcomes analyzed increase learning outcomes, student activities and teacher activity. The results showed an increase in learning from the first cycle to the second cycle. The large increase in learning outcomes of the science base score, UH1 and UH2. Basic scores are taken from the average daily test before applied science students learning model to apply the approach of Contextual Teaching Learning (CTL) is 59.85. In the first cycle the average value of daily tests was 61.50, an increase of the value of learning outcomes of students studying science at the previous 2.76%. In the second cycle the average student learning outcomes IPA was 72.00 daily test the learning outcome of the first cycle to the second cycle of 17.07%. Improving student learning outcomes as a whole amounted to 19.83%. Activity increased student learning first cycle of meetings 1 with average 50.42% to 63.13%, while for the second cycle increased from the third meeting with an average of 74.17% to 83.33%. The activities of teachers of the first cycle increased from the first meeting with an average of 62.50% to 72.50%, while the second cycle increased from the third meeting with an average of 85.00% to 90.00%. For student activity based on the results of the study an increase in activity of students in the learning process, while the teacher found increased activity in terms of guiding students in the learning process has been very good and the teachers are also no longer as the central conduit of information. Based on the results of the study it can be concluded that the application of the approach of Contextual Teaching and Learning (CTL) can improve learning outcomes IPA grade IV SDN 016 Pandan Air.Keywords : Model Approach Contextual Teaching and Learning (CTL), IPA Learning Outcomes